Geography and the evolution of rural nonfarm sector in the Philippines, 1988-2006 - Estudillo, Jonna P.; Ramos, Charity Gay; Otsuka, Keijiro ([Quezon City] School of Economics, University of the Philippines, 2009)
This paper aims to assess the changing impact of distance on the development of rural labor force between the farm and nonfarm sectors in the Philippines using provincial-level data from 1988 to 2006. The impact of distance of a province from a major city on the growth impact of its rural nonfarm sector did not change over time because of the concentration of infrastructure developments in provinces located in major cities.
Title was 'Philippine Review of Business and Economics' until 1979. Title changed to 'Philippine Review of Economics and Business' from 1980-2000, and again changed to 'Philippine Review of Economics' since 2001.
Includes bibliographical references (page 216-219)
Keywords: Industrial development projects -- Philippines -- Sociological aspects; Rural development projects -- Philippines -- Sociological aspects; Community development -- Philippines